2014
DOI: 10.1051/parasite/2014043
|View full text |Cite
|
Sign up to set email alerts
|

Activity of benzimidazoles againstDientamoeba fragilis(Trichomonadida, Monocercomonadidae)in vitroand correlation of beta-tubulin sequences as an indicator of resistance

Abstract: Recently, Dientamoeba fragilis has emerged as a significant and common enteropathogen. The majority of patients with dientamoebiasis present with gastrointestinal complaints and chronic symptoms are common. Numerous studies have successfully demonstrated parasite clearance, coupled with complete resolution of clinical symptoms following treatment with various antiparasitic compounds. Despite this, there is very little in vitro susceptibility data available for the organism. Benzimidazoles are a class of antipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To date, studies of the effectiveness of treatment of D. fragilis have been small (most include fewer than 100 subjects), they tend to study a heterogeneous population (studies in children, children and adults and adults), and generally include retrospective case series (CDC-Centers for Disease Control, 2017; van Gestel et al, 2018). The eradication rates reported vary greatly, with elevated rates of therapeutic failure (up to 80%) (Nagata et al, 2012; Stark et al, 2014; van Gestel et al, 2018). With regard to the antiparasitic drugs used, metronidazole has been studied more frequently, with eradication rates ranging from 52% to 85% (Banik et al, 2011; Engsbro et al, 2012; Kurt et al, 2008; Röser et al, 2014; Schure et al, 2013; Damien Stark et al, 2010; van Hellemond et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, studies of the effectiveness of treatment of D. fragilis have been small (most include fewer than 100 subjects), they tend to study a heterogeneous population (studies in children, children and adults and adults), and generally include retrospective case series (CDC-Centers for Disease Control, 2017; van Gestel et al, 2018). The eradication rates reported vary greatly, with elevated rates of therapeutic failure (up to 80%) (Nagata et al, 2012; Stark et al, 2014; van Gestel et al, 2018). With regard to the antiparasitic drugs used, metronidazole has been studied more frequently, with eradication rates ranging from 52% to 85% (Banik et al, 2011; Engsbro et al, 2012; Kurt et al, 2008; Röser et al, 2014; Schure et al, 2013; Damien Stark et al, 2010; van Hellemond et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The transmission and biological cycle of D. fragilis have not been reported, although fecal–oral transmission is most probable (Munasinghe et al, 2013; Stark et al, 2016). In recent years, a cystic form of infection has been reported, which may explain how D. fragilis remains in the environment and could be a vehicle that mediates transmission between hosts (Stark et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of several benzimidazoles against D. fragilis was tested in vitro using four clinical isolates (198). Susceptibility testing showed that albendazole, flubendazole, mebendazole, nocodazole, triclabendazole, and thiabendazole had no effect against Dientamoeba.…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%
“…Two beta-tubulin transcripts were sequenced from a clinical isolate of D. fragilis genotype 1, and the amino acid sequences of each beta-tubulin predicted susceptibility to benzimidazoles. This suggests that beta-tubulin sequences cannot be used as reliable markers for prediction of resistance to benzimidazoles in trichomonads (198). It should be noted that while Trichomonas and Giardia are susceptible to benzimidazoles, H. meleagridis is resistant, although the exact mechanism of resistance remains unknown (198).…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%